The menace of pornography - Abdul Razak, Rafidah; Rokis, Rohaiza (IIUM Press, International Islamic University Malaysia, 2017)
Pornography is a social issue that requires for a special attention. In this advanced technological age, various telecommunication channels provide sorts of pornographic contents and images to people. Youngsters are the most affected. This book is an outcome of an empirical research project that examines the attitudes toward pornography among IIUM students. The data was obtained from 240 Malay male and female students of Human Sciences undergraduate programme at the International Islamic University Malaysia (IIUM) within the age-range of 20 to 25 years. Today, technology in particular the Internet is a contributory factor to the development of pornography. Amounted to about 4.2 million web pages, pornography on the Internet has the biggest consumers who are from diverse socio-demographic backgrounds. Despite the legal and Islamic prohibitions, many Malaysians and Muslims, in particular are consuming the sexually explicit materials (SEM) containing pornographic images and explicit scenes in their daily lives. There are three objectives of the research, firstly to identify the attitudes of students toward pornography and its effects; secondly to compare the documented effects of pornography with the attitudes of the students; and thirdly to create awareness of the harmful effects of pornography to society at large. In collecting the data, the two methods of research applied were questionnaire and semistructured interview. From non-random sampling of 240 students who were involved in the quantitative research, ten of them were interviewed. The major finding of the research showed that pornography is not always positive to the students. The effects of pornography are numerous. The majority of the respondents believed that the consumption of pornographic materials may lead to pornographic and sexual addiction; breakdown of family institution; aggressive behaviour toward women; involvement in sexual crimes; and the false perceptions of sex and women among the young individuals. Towards the end of the research, useful strategies that could control the problem of pornography in Malaysia were proposed. Among the proposals suggested by the respondents are sex education in schools, frequent police raids and enhancement of spiritual values of the society.